TRANSGENERATIONAL TRAUMA & RESILIANCE: THE UNTHOUGHT KNOWN - NAMELESS RUPTURE AND REPAIR (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2021)
All forms of oppression, whether is racism, genocide, or exclusivity of a dominant group within a region or a country, is a system that impacts everyone within it, pervasively, deeply, and for the dominant group, often unconsciously. The transgenerational trauma is experience of violence perpetrated upon parents and transmitted to subsequent generations, a colonized mind of unbearable and unprocessed psychic experience without conscious knowledge and interest in being processed and transformed. The last 20 years research intensified on this topic, addressing the questions: How do we understand the vicissitudes of historical trauma? How do we help people create a vital connection to the “Other” given the shifts and splits still alive in today’s culture? And most importantly, how do we understand and facilitate a relationship to a deeply felt, individual sense of self so that each may live a more authentic, meaningful life? The author describes what is trauma, how transgenerational transmission manifests, what are the causes, and how resilience develops. The final focus is on the psychology of the Macedonian ethnic identity, specifically reflecting on the Aegean Exodus and the wounds of the transgenerational trauma among this ethnic group.
Keywords: trauma; transgenerational transmission; resilience; Macedonian identity; Aegean exile